Site-specific antibody-drug conjugate heterogeneity characterization and heterogeneity root cause analysis. Issue 6 (18th August 2019) - Cao, Mingyan; De Mel, Niluka; Jiao, Yang; Howard, James; Parthemore, Conner; Korman, Samuel; Thompson, Christopher; Wendeler, Michaela; Liu, Dengfeng
ABSTRACT: Site-specific antibody-drug conjugates (ADCs) are designed to overcome the heterogeneity observed with first-generation ADCs that use random conjugation to surface-exposed lysine residues or conjugation to interchain disulfide bonds. Despite significantly enhanced homogeneity, however, the production of site-specific ADCs yields some process-related species heterogeneity, including stereoisomers, unconjugated antibody, underconjugated species, and overconjugated species. An elevated level of size variants, such as heavy chain-light chain species (half ADC), heavy chain-heavy chain-light chain species, and light chain species, is also observed with the final site-specific ADC product. To understand the root cause of heterogeneity generated during the ADC conjugation process, we designed time-course studies for each conjugation step, including reduction, oxidation, conjugation, and quenching. We developed both non-reduced peptide map and LabChip-based capillary electrophoresis sodium dodecyl sulfate methods for time-course sample analysis. On the basis of our time-course data, the half ADC and unconjugated antibody were generated during oxidation as a result of alternative disulfide bond arrangements. During oxidation, two hinge cysteines formed an intra-chain disulfide bond in the half ADC, and three inter-chain hinge disulfide bonds were formed in the unconjugated antibody. Time-course data also showed that the elevated level of size variants, especially heavy chain-heavy chain-light chain species and light chain species, resulted from the quenching step, where the quenching reagent engaged in a disulfide bond exchange reaction with the ADC and broke the disulfide bonds connecting the heavy chain and light chain. Underconjugated and overconjugated species arose from the equilibrium established during the conjugation reaction.